Watching English Movies to Enhance EFL Students’ Listening Ability - Abdul Karim, Sayit; Kumalasari, Diva; Lailla Ningrum, Putri; Qurrota A’yun, Silvianida; Justinio, Michael; Amin Aziz, Yek (ITScience (Information Technology and Science), 2024)
This research explores EFL students' perceptions of watching English movies to improve their English listening ability. This study utilizes a quantitative approach and the data were gathered through an online survey, using a questionnaire from Google Forms which uses a Likert-scale. 34 students (24 females and 10 males) from the English Language Education Study Program (ELESP) were involved in the data-gathering process. Furthermore, the questionnaire consists of five questions asking about how they perceive the use of English-based movies to improve their listening ability. The findings revealed that 52.9% or 18 respondents strongly agree and 47.1% or 16 respondents agree with the statement that a movie is an interesting medium for improving English skills. Meanwhile, 41.2%, or 14 respondents strongly agreed and 58.8%, or 20 respondents agreed they were interested in watching English movies because it could improve their listening skills. Then, 38.2%, or 13 respondents strongly agreed and 61.8% or 21 respondents agreed that watching English movies made them interested in learning English. Furthermore, 44.1% or 15 respondents strongly agreed and 55.9% or 19 respondents agreed that watching English movies can teach them to listen to English conversations. The results of the last question showed that 23.5% or 8 respondents strongly agree and 76.5% or 26 respondents agree that watching English movies can make them understand the movie plot they are watching.